Analisis Metode Baru Dakwah Hanan Attaki Di Era Konvergensi Media - Muhamad Parhan; Prihatini Riezky A; Sarah Alifa (KOMUNIDA : Media Komunikasi dan Dakwah, 2020)
Da'wah in the digital era and utilizing the development of information and communication technology, adding a new portion to broadcast Islam to the public. The existence of technology gave birth to the internet and new media in disseminating information. Hanan Attaki is one of the clerics today who is close to millennial audiences who cannot get far from social media in their daily lives. Therefore, this study aims to find out how the new method used by Hanan Attaki in broadcasting Islamic broadcasting in the era of media convergence. The method in this study uses a mix method, which is a combination of quantitative research methods by distributing questionnaires with Google Form and qualitative research methods by analyzing content on the Instagram account @hanan_attaki. The results obtained in this study Hanan Attaki is a preacher / cleric who is famous among young people, his style of preaching that now makes Hanan Attaki has a lot of followers on social media Instagram. His Instagram account is also intense in uploading content about Da'wah.